PARTISIPASI PETANI DALAM PENGELOLAAN HUTAN KEMASYARAKATAN DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Sagita, Merki Natasya; Akhbar, Akhbar; Muis, Hasriani (Universitas Tadulako, 2019)
Community Forestry (HKm) is a state forest aimed at empowering, increasing the capacity and independence of local communities to obtain the benefits of forest resources optimally and fairly. Community forest management is one solution to improve community welfare and is a concrete form of community participation in the implementation of forestry development. Community participation in community forest management is one of the social capital that has been developed integratively through various creative activities in order to utilize natural resources sustainably and sustainably. The purpose of this study was to determine the level of participation of community forest farmers in Labuan Toposo Village, Labuan Subdistrict, Donggala Regency. The method used in this study is descriptive method. Data collection is done by observation or direct observation in the field and conducting interviews with farmers (Respondents). The population in this study were farmers in Labuan Toposo Village. Sampling in this study using purposive sampling method or with intentional namely by selecting farmers who are members of the Sisere Jaya Forest Farmer Group with 30 respondents. The research data analysis was used to answer the research objectives that had been made using quantitative descriptive and qualitative descriptive analysis. The level of participation in Community Forest Management is classified as high with a percentage of 76.67%, and the level of participation of farmers in community forest management is at the planning stage of entering the Partnership level. Power is channeled between government negotiations and farmers. The government imposes farmers as work partners, they together work together in compiling and implementing work programs.Keywords: Community Forestry, Participation, Forest Farmers, Forest Management